The Dynamic Relationship Between Public Education Expenditure and Economic Growth: A Case Study of Iraq (2010–2024) - Nagham Aziz Mohamad Ali (Indonesian Journal of Law and Economics Review, 2026)
General Background: Public expenditure on education is an important investment in human capital and economic development. Specific Background: Iraq experienced fluctuations in education expenditure and economic growth during 2010–2024 due to oil dependency, political instability, and financial crises. Knowledge Gap: Limited studies explain the dynamic relationship between educational spending, human capital, and economic growth in Iraq under unstable economic conditions. Aims: This study examines the relationship between public education expenditure and economic growth in Iraq by analyzing educational, economic, and policy indicators. Results: The findings show that educational spending has a positive long-term relationship with economic growth, but its contribution is constrained by weak infrastructure, administrative inefficiency, corruption, curriculum gaps, and reliance on oil revenues. The study also identifies gradual improvements in literacy, enrollment, education quality, and graduate employment indicators, while technical and vocational education supports productivity and economic diversification. Novelty: This study combines educational expenditure trends, human capital indicators, and sectoral economic analysis to explain the multidimensional relationship between education and growth in Iraq. Implications: Improving educational quality, governance, vocational training, and equitable resource allocation is essential to strengthen sustainable economic growth. Highlights: • Educational expenditure in Iraq showed a positive long-term connection with human capital development and productivity.• Economic expansion remained unstable because of oil dependency, political instability, and financial fluctuations.• Technical and vocational training supported workforce readiness and economic diversification strategies. Keywords: Education Expenditure, Economic Growth, Human Capital, Vocational Education, Public Policy